PENERAPAN PRECEPTORSHIP MODEL TERHADAP KOMPETENSI DAN PERFORMANCE MAHASISWA: COMPETENCY OUTCOME AND PERFORMANCE ASSESSMENT MODEL APPROACH - RR Viantika Kusumasari (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2017)
Background: Clinical teaching that is unsupportive will affect the competency and perfomance of nursing students. Indonesian Ners Competency Test showed a result that is not maximum, the graduation data in June and November 2014 were 57.81% and 46.20%. Precetorship model is a clinical teaching model that can be applied to improve the competency and perfomance of nursing students.Objective: To determine the effect of the application of precetorship models toward competency and perfomance of nurses profession students at Institute of Health Science Surya Global Yogyakarta with COPA model approach.Method: The design used quantitative research “quasy experimental post-test-only-control group” and a descriptive survey. The sampling technique used quota sampling. The respondents in intervention group were 56 nursing students and in the control group were 28 nursing students. The research instrument is assessment sheet that was  developed from COPA model and the observation guidelines sheet. Data analysis  used independent t-test.Results: The results showed  the competency and perfomance of nursing students in the intervention group is higher than the control group. The average value of intervention group was88,18+4,94, while the control group was 73,21+5,46. The highest difference value of assessment item of COPA model on humanistic caring and relationship skill was 17.00and the lowest value on teaching skills was 14,28.Conclusion: There is the effect of the application of precetorship model toward the competency and perfomance of nurses profession students at Institute of Health Science Surya Global Yogyakarta with COPA model approach.